Assessing the Effectiveness of Local Government Decentralization in Enhancing Public Service Delivery in the Philippines - Juan Dela Cruz (Mahogany Journal De Social, 2024)
This study examines the effectiveness of local government decentralization in enhancing public service delivery in the Philippines. Although decentralization is widely regarded as a strategy to improve governance responsiveness and efficiency, its outcomes remain uneven across local government units (LGUs). This research adopts a qualitative descriptive approach using document analysis of policy frameworks, government reports, audit findings, and academic literature. Through thematic analysis and a comparative perspective, the study identifies key structural challenges shaping decentralization outcomes. The findings show that decentralization has not consistently improved service delivery but instead has amplified disparities between high-capacity and low-capacity LGUs. Successful cases are largely driven by strong local leadership and institutional capacity rather than by the effectiveness of decentralization policy itself. Moreover, increased fiscal autonomy has not always translated into better outcomes due to weak administrative systems, limited accountability mechanisms, and fragmented intergovernmental coordination. The study concludes that decentralization is a capacity-dependent process and highlights the need for institutional strengthening, improved coordination, and performance-based governance to achieve more equitable and effective public service delivery.